Revitalisasi Nilai-Nilai Pancasila Dalam Penguatan Etika Kelembagaan Negara Di Indonesia - Hadi Karyono; Mahmuda Febriharinia Pancawisma; Salma Nur Hanifah (PMIH Untag Semarang, 2025)
The revitalization of Pancasila values has become an urgent necessity in strengthening the ethics of state institutions in Indonesia. In the current development of state governance practices, there appears to be a shift in institutional orientation that tends to be pragmatic and less grounded in constitutional moral values. Pancasila, as an ideology and the foundation of the state, is not only the source of the highest law but also a source of public ethics that guides the behavior of state institutions. This article analyzes how Pancasila values can be re-internalized into the ethics of state institutions through a normative legal approach, emphasizing the moral responsibility and integrity of state administrators. By examining legal doctrines, the constitution, and state governance practices, this study finds that strengthening institutional ethics must begin with the reconstruction of Pancasila values as a living and operational constitutional ethical foundation.